Effect of Ni content on microstructure and properties of Co-based superalloys - ZHOU Pengjie; SONG Dehang; WU Haibin; GAO Xinkang; NOBUFUMI Ueshima; KATSUNARI Oikawa (Journal of Aeronautical Materials, 2019)
Co-based superalloys casting ingots were prepared by vacuum smelting furnaces, and the influence of Ni content on the microstructure and lattice misfit of Co-based superalloys were studied by X-ray diffraction analysis (XRD) and scanning electron microscope (SEM). The effect of Ni content on the properties of Co-based superalloys was studied by high temperature compression test. The results show that the average size of the γ′ phase increases with the increment of Ni content. When the Ni content rises from 0% to 15%, the volume fraction of the γ′ phase in the alloy increases gradually, which peaks at 15% Ni content.After that the volume fraction of the γ′ phase decreases slightly when the Ni content increases to 20%.When the Ni content increases from0 to 10%, the lattice misfit between γ/γ′ phase decreases.While the misfit of the γ/γ′ phase increases slightly when the Ni content raises to 20%.The Ni content increases from 10% to 15%, the lattice misfit of the γ/γ′ phase begins to decreases again. Through the test of high temperature compression of the alloy, the yield strength of the alloy with 5% Ni content is the highest.